The explanatory method's relationship to the motivation of academic achievement among a sample of tenth grade students in the governorate of Muscat in the Sultanate of Oman - Ahmed Salim Khamis, Al-Qalhati; Abd Karim, Aishah Hanim; Hassanein, Ismaiel (OCERINT International Organization Center of Academic Research, 2022)
This quantitative study discusses the concept of the explanatory method and its relationship to the level of academic achievement motivation among tenth grade students in the Governorate of Muscat. The problem stems from the low motivation for academic achievement, which negatively affects their academic rates; With distortions in the method attributed to success and failure. Therefore, the study aims to diagnose the level of the explanatory style, the level of students' academic achievement motivation, and to measure the significance of the differences between males and females. The study adopted the descriptive correlative approach. The total population was (9473) male and female students. The researcher chose a random sample of (369) male and female students, according to the table of Krejcie, & Morgan. The researcher used two scales; The first to measure the explanatory style of success and failure, prepared by the researcher; It consists of (25) statements divided into four domains. The second scale: for the academic achievement motivation, prepared by Al-Mashrafi; It consists of (20) statements distributed into four domains. Statistical methods: Pearson's correlation coefficient, Cronbach's alpha coefficient, (Spearman-Brown) equation, t-test. The study findings revealed that: The level of the explanatory style in all dimensions was optimistic: in the subjectivity dimension, in the continuity dimension, in the generalization, and in the controllability. The level of achievement motivation of the study sample was high in all dimensions of the scale: academic ambition, goal orientation, need for achievement, and cognitive motivation. There are statistically significant differences in the level of explanatory style in favor of the male students. And there are no differences in achievement motivation among male and female students.